Penerapan Bioteknologi DNA Rekombinan: Pengembangan Vaksinasi COVID-19 - Ni Putu Pranita; Rani Himayani; Rizki Novtarina; Robby Cahyo Nugroho; Helmi Ismunandar (CV. Jasa Sukses Abadi, 2021)
The role of science and technology in all sectors is getting bigger and bigger. The development of science and technology encourages innovation in all fields including in the health sector. Specifically regarding advances in science and technology in the health sector, it relies on research by experts, including medical biotechnology. One form of utilization of medical biotechnology is the development of vaccinations. In dealing with the Covid-19 pandemic, the application of medical biotechnology can be done by developing vaccinations using recombinant DNA technology. All researchers around the world in all related fields such as genomic and structural biology experts work together to develop this vaccine. Of these several agencies, InoVio as one of the research agencies developed a DNA vaccine. The DNA vaccine has several advantages, including fast production time and formulation, can be produced in large quantities, is safer, more stable to temperature so that it is easy to store and transport. Currently the DNA vaccine for the SARS-CoV-2 virus is still in the next clinical trial phase and is mass produced for emergency use.The role of science and technology in all sectors is getting bigger and bigger. The development of science and technology encourages innovation in all fields including in the health sector. Specifically regarding advances in science and technology in the health sector, it relies on research by experts, including medical biotechnology. One form of utilization of medical biotechnology is the development of vaccinations. In dealing with the Covid-19 pandemic, the application of medical biotechnology can be done by developing vaccinations using recombinant DNA technology. All researchers around the world in all related fields such as genomic and structural biology experts work together to develop this vaccine. Of these several agencies, InoVio as one of the research agencies developed a DNA vaccine. The DNA vaccine has several advantages, including fast production time and formulation, can be produced in large quantities, is safer, more stable to temperature so that it is easy to store and transport. Currently the DNA vaccine for the SARS-CoV-2 virus is still in the next clinical trial phase and is mass produced for emergency use.